2017
DOI: 10.1080/10615806.2017.1385065
|View full text |Cite
|
Sign up to set email alerts
|

The role of therapist support on effectiveness of an internet-based modular self-help intervention for adjustment disorder: a randomized controlled trial

Abstract: The present study supported the effectiveness of the BADI intervention. Our findings also indicated that adding therapist support to the standard BADI intervention did not significantly improve the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…This low intensity ICD-11 AjD intervention can be used without therapist support. Findings of the recent study ( N  = 1077) revealed moderate effect sizes ( d  = 0.53–0.64) of the BADI intervention on AjD symptoms in this study (Eimontas et al, 2017). Furthermore, additional psychologist support was not contributing significantly to the outcomes of the intervention, indicating that internet-delivered self-help AjD interventions could be considered as a promising alternative in the treatment of AjD (Eimontas et al, 2017).…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…This low intensity ICD-11 AjD intervention can be used without therapist support. Findings of the recent study ( N  = 1077) revealed moderate effect sizes ( d  = 0.53–0.64) of the BADI intervention on AjD symptoms in this study (Eimontas et al, 2017). Furthermore, additional psychologist support was not contributing significantly to the outcomes of the intervention, indicating that internet-delivered self-help AjD interventions could be considered as a promising alternative in the treatment of AjD (Eimontas et al, 2017).…”
Section: Resultssupporting
confidence: 52%
“…The stressor list of the ADNM was used in nine reviewed studies. However, the number of stressors in the first part of the ADNM ranged considerably across different studies: 10 stressors (Bachem & Maercker, 2016; Bachem, Perkonigg, Stein, & Maercker, 2016), 13 stressors (Horn & Maercker, 2016), 15 stressors (Zelviene, Kazlauskas, Eimontas, & Maercker, 2017), 16 stressors (Glaesmer, Romppel, Brähler, Hinz, & Maercker, 2015), 17 stressors (Eimontas et al, 2017), and 19 stressors (Lorenz, Bachem, & Maercker, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations